Golden Horn Estuary: Description of the ecosystem and an attempt to assess its ecological quality status using various classification metrics - ALBAYRAK, S.; BALKIS, N.; BALKIS, H.; ZENETOS, A.; KURUN, A.; KARHAN, S.U.; CAGLAR, S.; BALCI, M. (Mediterranean Marine Science, 2010)
In this paper, we describe the pelagic and benthic ecosystem of the Golden Horn estuary opening into the Marmara Sea. To improve the water quality of the estuary, which had long been subject to severe anthropogenic pollution (industrial, chemical, shipping), industrial facilities were moved from the estuary in the 1980s, followed by a rehabilitation plan in the 1990s. Our results, based on chemical parameters and phytoplankton showed some signs of improvement of water conditions in the upper layer. However, macrozoobenthic findings of this study did not reflect such a recovery in bottom life. An approach to the Ecological Quality Status (EQS) assessment was performed by applying the biotic indices BENTIX, AMBI, BOPA, BO2A. Our final assessment was based on 'expert-judgements' and revealed a very disturbed overall ecosystem with 'bad' EQS for the station at the head of the estuary, 'poor' in the rest of the estuary and 'moderate' EQS only in the middle station.